Growth and Characteristics of Two Different Epichloë sinensis Strains Under Different Cultures - Luo, Yang; Tian, Pei (Frontiers in Microbiology, 2021)
In the present study, two Epichloë sinensis endophyte strains isolated from different Festuca sinensis ecotypes were inoculated on potato dextrose agar (PDA) and potato dextrose broth (PDB) media with or without (control) exogenous additives. After four weeks of growth, the growth (colony diameter, hyphal diameter, and mycelial biomass) and other characteristics (pH, antioxidant capacity, mycelial ion content, and hormone contents) were measured. The two E. sinensis strains exhibited significantly different performances (P<0.05) under the five treatments. The indices including colony diameter, mycelial biomass, scavenging ability of superoxide anion radicals and hydroxyl radicals, pH of culture filtrate, ion contents, hyphal diameter, and IAA, CTK, GA, and ABA contents were significantly different (P<0.05) between the two strains, although the performance was inconsistent. The culture conditions also had significant effects (P<0.05) on the hyphal diameter, mycelial biomass, and hormone content of the two strains. The mycelial biomass of the two strains in PDB was significantly higher (P<0.05) han that on PDA. Except for strain 1 with IAA treatment and strain 84F with control and VB1 treatments, the hyphal diameter of the two strains in PDB under the other treatments was significantly higher (P<0.05) than that on PDA. In most cases, the IAA, CTK, ABA, and GA contents in the mycelia on PDA of the two strains were significantly higher (P<0.05) than those in PDB. Exogenous additives had significant effects (P＜0.05) on the performance of the two E. sinensis strains. IAA and VB1 treatments significantly promoted (P＜0.05) the growth of the two strains on both PDA and PDB. IAA treatment also significantly increased the hyphal diameters of the two strains in PDB (P＜0.05). IAA and VB1 treatments significantly reduced (P＜0.05) the antioxidant ability of these two strains in PDB. NaCl and ZnCl2 treatments had significant inhibitory effects (P＜0.05) on fungal growth and promotion effects on the antioxidant ability of the two strains. The treatments also had significant effects (P＜0.05) on hyphal diameters and ion and hormone contents, although the effects varied with different indices.